(untitled) (Research, Society and Development, 2021)
The new coronavirus that causes Severe Acute Respiratory Syndrome (SARS-CoV-2), has expanded rapidly in Brazil and worldwide. Health services point out that the group most vulnerable to severe COVID-19 infection is the elderly. Social isolation measures, although protecting against contagion, have a direct impact on the functionality of the elderly, mainly on psychological and physical variables such as strength, balance, gait, and cardiorespiratory capacity, which are essential for carrying out daily activities. Purpose of the study was to describe the impacts of social isolation on the functionality of the elderly during the COVID-19 pandemic from a perspective based on the International Classification of Functionality (CIF). This is an integrative review. Studies that mentioned the descriptors "elderly" and "COVID-19" and that addressed the topic of social isolation and / or functionality and / or comorbidities were included. There was no restriction on the study design, language, and year of publication. The databases consulted were PubMed, Scopus, Science Direct and Google Scholar. 5057 studies were identified, 42 chosen by title and abstract. After rigorous reading in full, 7 met the objectives and were summarized in a table. Social isolation had psychological implications, sedentary behavior and reduced functionality in the elderly. Social isolation due to the COVID-19 pandemic has made the elderly population with sedentary habits, psychological and functional changes that interfere with daily activities. Oriented physical activity can be an important alternative to minimize the functional impacts of the elderly and assist in the biopsychosocial aspects recommended by the International Classification of Functionality.